Penguatan Pemahaman Restorative Justice Bagi Aparatur Desa dalam Penyelesaian Konflik Sosial dan Lingkungan - Mulyani Zulaeha; Muhammad Yasir; Muhammad Azianoor Ilmy; Achmad Faishal; Suprapto Suprapto; Anang Sophan Tornado; Soffyan Angga Fahlani; Cindyva Thalia Mustika (Pusat Riset dan Inovasi Nasional, 2026)
This community service program aimed to strengthen village officials’ understanding of restorative justice for resolving social and environmental conflicts in Gudang Hirang Village, Banjar Regency. The results indicated a significant improvement in the officials’ ability to identify minor conflicts, conduct neutral restorative justice-based mediation, and draft written agreements that prioritize victim recovery without recourse to formal judicial proceedings. Enhanced understanding of restorative justice directly contributed to community harmony in Gudang Hirang Village. A local wisdom-based dispute resolution mechanism involving village officials, community leaders, Babinsa, and Bhabinkamtibmas effectively prevented the escalation of social and environmental conflicts and resolved them through familial approaches. This model reduces court caseloads for minor cases while promoting active community participation in maintaining order and social justice. Program sustainability can be ensured through the establishment of a Restorative Justice House, the development of village mediation SOPs, and periodic mentoring by the service team, thereby institutionalizing restorative justice principles as the primary instrument for maintaining peace at the village level. The program employed lectures with PowerPoint presentations, case discussions, interactive question-and-answer sessions, and pre-tests and post-tests. Equipment used included laptops, microphones, a sound system, mobile phones, and an LCD projector.